1983
DOI: 10.1073/pnas.80.11.3158
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and genetic evidence for specific antiestrogen binding sites.

Abstract: In rat uterus and human breast cancer MCF-7 cell cytosol, the antiestrogens tamoxifen (Tam) and 4-hydroxytamoxifen (OH-Tam) bind to "antiestrogen binding sites" (ABS), which do not bind estradiol (E). Demonstrated in total cytosol by binding studies with radioactive antiestrogens in the presence of a large concentrationlof E, ABS can be physically separated from E-binding estrogen receptor (ER) by removing the latter with an E-containing bioaffinity adsorbent or with heparin-Sepharose gel. ABS concentration is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Since progesterone receptor is an estrogenstimulated protein (15, 19), we examined the effect of phenol red on progesterone receptor levels in MCF-7 cells. Basal progesterone receptor level was 3 times higher in control cells grown in medium containing 30 ,uM phenol red than in control cells grown in phenol red-free MEM (Table 1). Cells treated with 1 nM estradiol exhibited the same high level of progesterone receptor, regardless of whether phenol red was absent or present.…”
Section: Binding Affinity Of Phenol Red For the Mcf-7 Estrogenmentioning
confidence: 99%
See 2 more Smart Citations
“…Since progesterone receptor is an estrogenstimulated protein (15, 19), we examined the effect of phenol red on progesterone receptor levels in MCF-7 cells. Basal progesterone receptor level was 3 times higher in control cells grown in medium containing 30 ,uM phenol red than in control cells grown in phenol red-free MEM (Table 1). Cells treated with 1 nM estradiol exhibited the same high level of progesterone receptor, regardless of whether phenol red was absent or present.…”
Section: Binding Affinity Of Phenol Red For the Mcf-7 Estrogenmentioning
confidence: 99%
“…Effect of Phenol Red on Estrogen Receptor-Negative MDA-MB-231 Breast Cancer Cells. In order to confirm the estrogen receptor-mediated effect of phenol red, we examined the effect of 30 ,LM phenol red on MDA-MB-231 cells, which do not contain estrogen receptors and are reported to be estrogen-and antiestrogen-unresponsive (11,20). Fig.…”
Section: Binding Affinity Of Phenol Red For the Mcf-7 Estrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Other data, however, suggest that some of the effects of antioestrogens, on growth and cellular proliferation in particular, are considerably more complex than would be anticipated if these effects were mediated solely by the oestrogen receptor (Martin, 1981;Faye et al, 1983;, 1985Reddel et al, 1983Reddel et al, , 1985Sutherland et al, 1983a,b).…”
Section: Introductionmentioning
confidence: 99%
“…We first reported phenotypic evidence of this by isolating an AEBS-negative cell line Rtx-6 from MCF-7 cells (a human breast cancer cell line) that was resistant to tamoxifen. The Rtx-6 cells were similar to MCF-7 cells in their ER content and functionality, suggesting a correlative link between the lack of AEBS and the insensitivity of these cells to tamoxifen [10] and to a specific AEBS ligand [11,12]. Other studies have reported dose-dependent cytostatic and cytotoxic effects of anti-oestrogens on ER-negative lymphoid cells that contain a high level of microsomal AEBS, thus underlining the importance of AEBS in the mediation of growth control [12][13][14].…”
Section: Introductionmentioning
confidence: 80%